Welfare versus Market Access: The Implications of Tariff Structure for Tariff Reform. - Anderson, J; Neary, P (Boston College Department of Economics, 2004)
We show that the effects of tariff changes on welfare and import volume can be fully characterised by their effects on the generalised mean and variance of the tariff distribution. Using these tools, we derive new results for welfare- and market-access-improving tariff changes, which imply two "cones of liberalisation" in price space. Because welfare is negatively but import volume positively related to the generalised variance, the cones do not intersect, which poses a dilemma for trade policy reform. Finally, we show that generalised and trade-weighted moments are mutually proportional when the trade expenditure function is CES.